Osteopontin and Its Clinical Correlation to Type 1 Cardiorenal Syndrome: A Literature Review - Welliam, Yongki; Wungu, Citrawati Dyah Kencono; Susilo, Hendri (Universitas Muhammadiyah Surabaya, 2025)
Cardiorenal syndrome (CRS) is a spectrum of disorders involving both the heart and the kidneys, either acutely or chronically, in one organ that can lead to dysfunction in the other. Type 1 CRS, the most common CRS, is when acute heart dysfunction impacts acute kidney dysfunction, commonly known as acute kidney injury. Comorbidities involving these two significant organs contribute to a high patient mortality rate that requires a new potential diagnostic method. Biomarkers are one of the diagnostic modalities widely used in various diseases. Osteopontin (OPN) is a phosphorylated glycoprotein found primarily in bones and teeth that regulates mineralization. Osteopontin is known to be involved in describing various pathological changes in the body, including cardiovascular diseases. This review aims to evaluate the clinical correlation of OPN level changes with the occurrence of Type 1 CRS. The results indicate that OPN also plays a role in detecting the progression of cardiovascular disease towards renal injury. The imbalance in the function of OPN as a pro-inflammatory and anti-inflammatory agent increases the progression of kidney disease in patients. Further findings suggest that, more specifically, urinary OPN describes renal injury events in type 1 CRS patients.